Rantai Pasok Komoditas Pepaya California Di Desa Talawaan Kecamatan Talawaan Kabupaten Minahasa Utara - Liho, Anjani; Pakasi, Caroline Betsi Diana; Pangemanan, Paulus Adrian (AGRI-SOSIOEKONOMI, 2024)
This research aims to determine the supply chain for California papaya commodities in Talawaan Village, Talawaan District, North Minahasa Regency. The research was carried out from June to December 2023. The data analysis method used in the research was descriptive analysis using tables and charts. The data used is primary data and secondary data. Primary data was obtained directly from respondents by conducting interviews using a questionnaire. Secondary data was obtained from the Talawaan Village Office, Central Statistics Agency, and other sources related to research. The research results show that the California papaya supply chain in Talawaan Village consists of farmers, collectors, wholesalers and retailers. The flow of California papaya products starts from farmers who produce California papaya, collecting traders buy from farmers then sell to wholesalers and then to supermarkets to sell according to demand, then sell to consumers and farmers sell to retailers then sell to consumers. The financial flow starts from supermarkets which buy from wholesalers, then wholesalers buy from the financial flow flows from downstream to upstream starting from consumers to supermarkets then to wholesalers and to collecting traders and finally to farmers, then from retailers to farmers or from consumers directly to farmers. The flow of information flows from two directions, first from upstream to downstream, farmers provide information regarding the availability of supplies to collecting traders and retailers, then collecting traders contact wholesalers. Second, from downstream to upstream, wholesalers and retailers as well as consumers are looking for information about supply availability.